Analisis Biaya Diferensial Sebagai Alat Pengambilan Keputusan Jangka Pendek dalam Optimalisasi Laba pada Penggilingan Bakso Wonogiri di Bekasi - Nadia Istiqomah; Natalia Titik Wiyani; Iis Dewi Herawati (AKUNTANSI 45, 2025)
This study aims to analyze differential cost as a decision-making tool in the short term to optimize profit in the Bakso Wonogiri grinding business in Bekasi. Differential cost refers to the difference in costs arising from two or more alternative decisions, which is highly relevant in determining the most economically efficient production choice. The research method employed is a case study with a quantitative-descriptive approach, where data were collected through observation, interviews, and documentation related to production activities and the company’s cost structure. The results differential cost analysis of accepting the additional order results in a net profit of Rp.15,408,000, which is higher compared to rejecting the order, which yields a profit of Rp.13,080,000. Therefore, the differential profit of Rp.2,328,000 indicates that the more appropriate and profitable decision for the company is to accept the order. Analysis show that the use of differential cost analysis can provide a more accurate picture in selecting production alternatives that contribute the greatest profit. In this case, production decisions based on differential cost analysis were able to reduce operational costs without significantly sacrificing production volume, thereby increasing efficiency and profitability. This study recommends that the management of the grinding business consistently apply differential cost analysis in every short-term decision to achieve profit optimization in production performance.